Situational project management the dynamics of success and failure - Lehmann, Oliver F. (Best practices and advances in program management series, 2016)
To guide project managers in selecting the appropriate responses, Situational Project Management (SitPM) shows how to assess a given project, determine its unique characteristics, and select the appropriate methods to complete the project. With this book, projects managers can use SitPM to develop profiles of their projects on the basis of the projects' physical characteristics, the project teams' behavioral characteristics, the enterprise environment, and the market environments receiving project deliverables. These profiles help project managers to determine the appropriate project life cycle approach and leadership style. The book also explores various ways to engage stakeholders on the basis of a project's SitPM profile.